Immunization coverage in young children: a study nested into a health and demographic surveillance system in Burkina Faso - Ouédraogo, Nobila; Kagoné, Moubassira; Sié, Ali; Becher, Heiko; Müller, Olaf (The journal of tropical pediatrics, 2013)
Background: Reliable estimates of immunization coverage are the basis for rational policy making, program implementation and evaluation. Vaccination coverage is usually measured using administrative data or surveys, both having a number of methodological problems. Methods: We estimated vaccination coverage using a data set of 11 906 children aged <5 years from an existing Health and Demographic Surveillance System (HDSS) in north-western Burkina Faso. Data were collected from September 2008 to December 2009. Results: Vaccination coverage based on information from existing vaccination cards ranged from 80% (measles) to 94% (OPV1). When taking into consideration all information available (including BCG scars in children with and without vaccination card), full coverage in children aged 12-23 months was around 75%, with a significantly higher coverage in rural compared with urban areas. There were no differences in vaccination coverage between boys and girls. Conclusion: The study supports other studies that found vaccination coverage improvement in Burkina Faso recently. In addition, our study found slightly better vaccination coverage in rural compared with urban areas, which needs further consideration.
Gesehen am 09.12.2021